Analisis Risiko Fraud Laporan Keuangan Menggunakan Pendekatan Beneish M-Score Pada Perusahaan Teknologi Yang Terdaftar Di Bursa Efek Indonesia - Hun, Ketrin Marlita; Yohanes Demu, Minarni Anaci Dethan, (YUME : Journal of Management, 2026)
This study aims to analyze the risk of financial statement fraud in technology sector companies listed on the Indonesia Stock Exchange (IDX) using the Beneish M-Score approach. The study focuses on this sector due to its high growth characteristics, significant intangible assets, and competitive pressures that may increase the likelihood of financial statement manipulation. A descriptive quantitative method with purposive sampling was employed. The sample consists of seven digital platform–based technology companies observed from 2021 to 2024, resulting in 28 sets of financial statements. The analysis utilized eight Beneish M-Score ratios to classify companies as manipulators, grey, or non-manipulators. The results show varying levels of fraud risk across companies and periods. In 2021, four companies were classified as manipulators and three as non-manipulators. In 2022, the number of manipulators decreased to three. In 2023, only two companies remained in the manipulator category. In 2024, two manipulator and five non-manipulator companies were identified. The most influential variables contributing to high M-Scores were DSRI, AQI, and SGI, indicating increased receivables, reduced asset quality, and extreme sales growth. These findings highlight the importance of early fraud detection to enhance transparency, governance, and the reliability of financial reporting in the technology sector. Keywords: Beneish M-Score, fraud, financial statements, IDX, technology companies..